Research mapping of cannabinoids and endocannabinoid system in cancer over the past three decades: insights from bibliometric analysis - Tan, Yaqian; Xia, Hui; Song, Qi (Frontiers in Pharmacology, 2025)
BackgroundThe cannabinoids and endocannabinoid system are thought to play critical roles in multiple signaling pathways in organisms, and extensive evidence from preclinical studies indicated that cannabinoids and endocannabinoids displayed anticancer potential. This study aimed to summarize the research of cannabinoids and endocannabinoid system in cancer through bibliometric analysis.MethodsRelevant literature in the field of cannabinoids and endocannabinoid system in cancer published during 1995–2024 were collected from the Web of Science Core Collection database. VOSviewer and SCImago Graphica were applied to perform bibliometric analysis of countries, institutions, authors, journals, documents, and keywords.ResultsA total of 3,052 publications were identified, and the global output exhibited a generally upward trend over the past 3 decades. The USA had the greatest number of publications and citations in this research field. Italian National Research Council led in terms of publication, while Complutense University of Madrid had the highest total citations. Vincenzo Di Marzo was the leading author in this field with the greatest number of publications and citations. The co-occurrence of keywords revealed that the research frontiers mainly included “cannabinoids”, “endocannabinoid system”, “cancer”, “anandamide”, “cannabidiol”, “cannabinoid receptor”, “apoptosis”, and “proliferation”.ConclusionOur results revealed that the research of cannabinoids and endocannabinoid system in cancer would receive continuous attention. The USA and Italy have made remarkable contributions to this field, supported by their influential institutions and prolific scholars. The research emphasis has evolved from basic functional characterization to mechanistic exploration of disease pathways and translational applications within multidisciplinary framework.